Latin American Liberation Theology as a Transforming Political Theology: Diversity, Fragmentarity, Relevance - Silber, Stefan (Interreligious Studies and Intercultural Theology, 2018)
Latin American Liberation Theology is a transforming theology in two senses: It is able to transform reality, as it has shown in these past decades, and it is transforming itself. This article shows how both types of meaning interweave. The transformations of Liberation Theology enable it to continuously adapt itself to new challenges in history. At present, this global theological movement is diversifying, or even fragmenting, in order to propose creative and effective solutions to different problems. Specifically, the Option for the Poor, which is at Liberation Theology’s core, currently presents profound challenges to European and Western theologies.